PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA (BPD DALAM PENYELENGGARAAN PEMERINTAHAN DI DESA PANGKALAN PISANG KECAMATAN KOTO GASIB KABUPATEN SIAK - Lia Adrianti; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to investigate the implementation of the function of BPD in Pangkalan Pisang, and to determine what factors are driving and inhibiting execution of these functions. The factors driving the implementation of the function of BPD in mind that (1) Coordination and cooperation among agencies, (2) the ability and experience of the board BPD community organizations. While inhibiting factor, namely, (1) People do not fully understand the functions performed by the BPD, resulting in the execution of the function BPD often have a discrepancy or difference of the community, and (2) lack of facilities and infrastructure supporting the implementation of the function. Therefore, the presence of various factors driving and inhibiting the function execution Village Consultative Body (BPD), resulting in the implementation of these functions can be run and also sometimes hampered in its execution. The theory used is the theory siagian. This study used a qualitative descriptive data collection techniques of observation and interviews. The results showed that the implementation of the functions known BPD (1) Function village set rules less accomplished because of constraints in its implementation, namely the lack of facilities and infrastructure supporting the implementation of the function, (2) Function accommodate public aspirations less done because there are still problems in implementation, namely community not yet fully understand the functions performed by the BPD, so that in the process of accommodating and aspirations of society often gets disagreement or debate of society, (3) Implementation of the oversight function has been implemented with good fit because it supported the implementation of coordination and cooperation between agencies in the village. Keywords: Function, Implementation BPD